Habb-e-Asgand, polyherbal Unani formulation, protects liver and antioxidative enzymes against paracetamol induced hepatotoxicity. (April 2014) - Ali, Mehboob; Khan, Sagheer Ahmed; Chang, Peter S.; Haque, Rizwanul; Bhatia, Kanchan; Ahmad, Saif
Abstract Context: Habb-e-Asgand, a polyherbal Homeopathy/Unani drug from Hamdard Wakf Laboratory, India, used in arthritis, gout and joint pain, is a mixture of many herbal medicinal plants. Scientific attempts to test and validate its efficacy are meager. Objective: To evaluate the hepatoprotective and antioxidative potential of Habb-e-Asgand against paracetamol toxicity. Materials and methods: Swiss albino male mice (n = 5/group) were treated with Habb-e-Asgand (250 mg/kg, body weight (b.w.) in normal saline orally for 14 days followed by a single dose of paracetamol (400 mg/kg b.w./normal saline) intraperitoneally 24 h before euthanization. We estimated liver function (LFTs) using diagnostic kits, while antioxidant enzymes, cytochrome P450 (CYP) and lipid peroxidation (LPO) were measured using spectrophotometric methods. Results: Paracetamol alone induced LFTs enzymes significantly (p < 0.05 and p < 0.01, 0.001), serum glutamate pyruvate transaminase (SGPT, ∼70%), serum glutamate oxaloacetate transaminase (SGOT, ∼20%), alkaline phosphatase (ALP, ∼20%), total bilirubin (∼30%), CYP activity (∼50%) and LPO (∼45%), while it significantly inhibited the activity of antioxidant enzymes glutathione reductase (GR, ∼35%), glutathione peroxidase (GPx, ∼40%), glutathione S-tranferase (GST, ∼16%), catalase (CAT, ∼84%) and glutathione (GSH, ∼30%) contents. Habb-e-Asgand alone and in combination of paracetamol significantly (p < 0.05, 0.01, 0.001) decreased LFT levels (20–25%), CYP activity (∼45%) and LPO level (∼25%), while it induced antioxidant enzyme activity (GR, ∼15%; GPx, ∼17%; GST, ∼20% and CAT, ∼60%). Discussion: Paracetamol metabolites may be mediating production of reactive oxidant species (ROS) and liver injury, which are attenuated by Habb-e-Asgand antioxidant constituents. Conclusion: Habb-e-Asgand may be used as a prophylaxis for ROS related liver injury.